Viabilidade da seleção simultânea para produtividade de grãos e qualidade fisiológica de sementes em milho - Costa , Júlia Carvalho (2022)
Currently, the demand is not only for more productive corn hybrids, but also for those with high physiological seed quality. Seed quality is considered the sum of genetic, physical, physiological and sanitary attributes that directly interfere in plant vigor. Thus, the objective was to evaluate the physiological parameters of seeds of the parents and of the corn hybrids obtained in a program of reciprocal recurrent selection, through physiological analyzes and image analysis techniques, as well as to study the feasibility of simultaneous selection for quality Seed physiology and grain yield in two reciprocal recurrent selection programs in maize. Two experiments were carried out, one in the field in a randomized complete block design and the other in the laboratory in a completely randomized design. The evaluated traits in the field were days for female flowering, days for male flowering, insertion of the 1st ear, plant height, bedged plants, percentage of broken plants and prolificity. For physiological quality, the attributes germination at four days, germination at seven days, vigor by the cold test, emergence speed index and the ratio of the length of the aerial line to the length of the aerial part through the GroundEye® were obtained. The data were submitted to analysis of variance with the aid of the software R, and the effects were evaluated by the F test and Scott Knott, at the level of 5% probability. Heterosis was obtained as well as the analysis through the contrast between hybrids and reciprocals in order to test the maternal effect. The magnitudes of heterosis allow us to infer that the greater the number of selective and recombination cycles, the greater the average heterosis for the traits grain yield and seed germination. There was no significance for the maternal effect in any of the evaluated traits, although the average heterosis has differed when comparing the hybrids with the reciprocals. The correlated response estimates allow us to infer that the selection for grain yield reflects in gains in the physiological seed quality, depending on the selective cycle in which the breeding program are.